Burkina Faso : Staff Report for the 2000 Article IV Consultation and First Review Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2000)
Burkina Faso's sustained adjustment effort has been supported by the IMF under successive programs since 1991. Macroeconomic performance was favorable in 1999. Monetary policy is conducted at the regional level by the Central Bank for West African States and remained prudent. In 1999 and early 2000, the Burkinabe authorities strengthened the implementation of structural reforms, in particular as regards the civil service, the cotton sector, and the liberalization of the telecommunications sector. Executive Directors stressed the importance of reforms to strengthen the competitiveness of the economy.